Benefits of Early In-Hospital Antivenom Administration to Patients with Protobothrops mucrosquamatus Envenomation - Chuang, Po-Chun (Am J Trop Med Hyg, 2021)
Protobothrops mucrosquamatus is one of the common venomous snakes in Southeast Asia. This retrospective cohort study conducted in six medical institutions in Taiwan aimed to obtain information on the optimal management strategies for P. mucrosquamatus snakebite envenomation. Data were extracted from the Chang Gung Research Database from January 2006 to December 2016. The association between early antivenom administration and patient demographics, pain requiring treatment with analgesic injections, and hospital length of stay was analyzed. A total of 195 patients were enrolled; 130 were administered antivenom within 1 hour after emergency department arrival (early group), whereas 65 were treated later than 1 hour after arrival (late group). No in-hospital mortality was identified. The difference in surgical intervention rates between the early and late groups was statistically insignificant (P = 0.417). Compared with the early group, the late group showed a higher rate of antivenom skin test performance (46.9% versus 63.1%, respectively, P = 0.033), longer hospital stay (42 ± 62 hours versus 99 ± 70 hours, respectively, P = 0.016), and higher rate of incidences of pain requiring treatment with analgesic injections (29.2% versus 46.2%, respectively, P = 0.019). After adjusting for confounding factors, early antivenom administration was associated with decreased pain requiring treatment with analgesic injections (adjusted odds ratio: 0.51, 95% CI: 0.260–0.985). Antivenom administration within 1 hour of arrival was associated with a decreased likelihood of experiencing pain and hospital length of stay in patients with P. mucrosquamatus snakebites. Antivenom skin testing was associated with delays in antivenom administration.